2004
DOI: 10.1038/sj.ejcn.1601957
|View full text |Cite
|
Sign up to set email alerts
|

Trigonelline is not responsible for the acute increase in plasma homocysteine following ingestion of instant coffee

Abstract: Objective: To determine whether trigonelline contributes to the effect of coffee on homocysteine (Hcy). Design and interventions: This was a randomised crossover study. Subjects consumed 50 mg trigonelline, 5 g of instant coffee (E50 mg trigonelline) or water, consumed as a single dose in 100 ml, with 1 week between each treatment. Blood samples were drawn fasting and hourly for 8 h. Urine samples were collected pretreatment and every 2 h for 8 h. Setting: Christchurch Clinical Studies Trust, Christchurch, New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Coffee consumers also appear to be at an increased risk of higher homocysteine concentrations, an independent risk factor for CVD (Strandhagen and others ; Strandhagen and others ; Slow and others ). This relationship may be driven by the chlorogenic acid (Piters and others ) rather than the trigonelline content of coffee (Slow and others ), but, can be modified by folic acid (Strandhagen and others ), particularly in those with the TT polymorphism of the methylenetetrahydrofolate reductase (MTHFR) gene which codes for the MTHFR enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Coffee consumers also appear to be at an increased risk of higher homocysteine concentrations, an independent risk factor for CVD (Strandhagen and others ; Strandhagen and others ; Slow and others ). This relationship may be driven by the chlorogenic acid (Piters and others ) rather than the trigonelline content of coffee (Slow and others ), but, can be modified by folic acid (Strandhagen and others ), particularly in those with the TT polymorphism of the methylenetetrahydrofolate reductase (MTHFR) gene which codes for the MTHFR enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that coffee raises homocysteine levels [7][8][9] and this increase can be seen within a few hours after ingestion [29,30] . It is thought that the chlorogenic acid and the caffeine in the coffee mediate this effect [29,31] .…”
Section: Discussionmentioning
confidence: 99%
“…The participant sample had a mean age of 79.3 years (range 67-95 years) and a mean of 13.6 years of education (range 7-22 years). There were 34 males and 55 females in the study with a mean Mini-Mental State Examination (MMSE) score of 28.8 (range of [24][25][26][27][28][29][30]. Inclusion criteria were age 6 60, no medical condition affecting cognition, ability to understand study procedures and informed consent to participate in the study, adequate motor and sensory capabilities (corrected or uncorrected) to perform neuropsychological testing and fluency in English.…”
Section: Participantsmentioning
confidence: 99%
“…An effect on glucose metabolism was also suggested for two other coffee compounds: trigonelline and magnesium. Trigonelline is a precursor of vitamin B 3 and represents about 1% of the dry weight of roasted coffee beans 114 ; its content in coffee ranges from 50 mg to 100 mg per cup 96,115,116 . An experimental study conducted in an animal model showed that trigonelline exerts a hypoglycemic effect 117 .…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…Trigonelline is a precursor of vitamin B3 and represents about 1% of the dry weight of roasted coffee beans 114 ; its content in coffee ranges from 50 mg to 100 mg per cup. 96,115,116 An experimental study conducted in an animal model showed that trigonelline exerts a hypoglycemic effect. 117 However, these data have not been confirmed in human studies; in fact, supplementation with high doses of trigonelline in humans had no effect on glucose metabolism, except in the very short term (15 min after glucose load).…”
Section: Effects On Glucose Metabolism: Can the Paradoxical Effect Ofmentioning
confidence: 99%